KEMATIAN ANAK DAN FAKTOR SOSIAL EKONOMI TERHADAP NILAI ANAK SEBAGA DAMPAK BENCANA DI KOTA PALU - Rahman, Abd; Arifuddin, Adhar; Vidyanto, Vidyanto; Nur, A Fahira; Maryama, Indah; Arifuddin, Hidayanti; Dyastuti, Nur Eka (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2023)
This study aimed to determine the relationship between child mortality and socioeconomic factors on the value of children in mothers in Palu. This type of research is a survey research with a cross-sectional design. This research was conducted in Palu City. Participants in this study amounted to 382 mothers. The sampling technique used proportional stratified random sampling. The chi-square test results showed that the child mortality variable had a very significant relationship with the child's score with a significance level of 0.001 or <0.05. Furthermore, socioeconomic factors, in general, are related to the value of the child, where age and education have a significant relationship to the value of the child, with each significance value being 0.029 or <0.05 and income is not related to the value of the child because the significance is >0.05 or 0.061. The results of this study are expected to be a reference or guide for the government that the assessment of families, especially mothers of children, will impact high fertility rates and the desire to have children in disaster-affected areas based on child mortality and socioeconomic factors.